Field Evaluation of Column CO2 Retrievals From Intensity‐Modulated Continuous‐Wave Differential Absorption Lidar Measurements During the ACT‐America Campaign. Issue 12 (8th December 2020) - Campbell, Joel F.; Lin, Bing; Dobler, Jeremy; Pal, Sandip; Davis, Kenneth; Obland, Michael D.; Erxleben, Wayne; McGregor, Doug; O'Dell, Chris; Bell, Emily; Weir, Brad; Fan, Tai‐Fang; et al.
Abstract: We present an evaluation of airborne intensity‐modulated continuous‐wave (IM‐CW) lidar measurements of atmospheric column CO2 mole fractions during the Atmospheric Carbon and Transport–America (ACT‐America) project. This lidar system transmits online and offline wavelengths simultaneously on the 1.57111‐μm CO2 absorption line, with each modulated wavelength using orthogonal swept frequency waveforms. After the spectral characteristics of this system were calibrated through short‐path measurements, we used the HITRAN spectroscopic database to calculate the average‐column CO2 mole fraction (XCO2 ) from the lidar‐measured optical depths. Using in situ measurements of meteorological parameters and CO2 concentrations for calibration data, we demonstrate that our lidar CO2 measurements were consistent from season to season and had an absolute calibration error (standard deviation) of 0.80 ppm when compared to XCO2 values calculated from in situ measurements. By using a 10‐s or longer moving average, a precision of 1 ppm or better was obtained. The estimated CO2 measurement precision for 0.1‐, 1‐, 10‐, and 60‐s averages was determined to be 3.4, 1.2, 0.43, and 0.26 ppm, respectively. These correspond to measurement signal‐to‐noise ratios of 120, 330, 950, and 1, 600, respectively. The drift in XCO2 over 1‐hr of flight time was found to be below 0.1 ppm. These analyses demonstrate that the measurement stability, precision, and accuracy are all well below the thresholds needed to study synoptic‐scale variations in atmospheric XCO2 . Key Points: Demonstrate the MFLL laser spectrometer for use in column CO2 retrievals Demonstrate the viability of this instrument for use in ACT America project goals Provide a methodology for doing CO2 or perhaps other types of retrievals using lidar